HUBUNGAN PEMAHAMAN PERKAWINAN DENGAN KESIAPAN KEHIDUPAN BERKELUARGA SISWA KELAS XII SMK NEGERI 6 PADANG TAHUN AJARAN 2026/2027 - Afni, Jumarotul; Pria Pandri, Desep; Rismi, Ridho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between marriage understanding and family life readiness among grade XII students at SMK Negeri 6 Padang for the 2026/2027 academic year. This research employed a quantitative method with a correlational approach, utilizing a sample of 215 respondents selected through proportional random sampling from a total population of 467 students. The research instrument was a Likert-scale questionnaire that had undergone validity and reliability testing. Descriptive analysis results indicate that the marriage understanding variable has a mean score of 76.32, while the family life readiness variable has a mean score of 100.21. Based on the correlation test results, it is concluded that there is a positive and significant relationship between students' marriage understanding and their family life readiness. This implies that the higher the students' understanding of marriage, the higher their level of readiness in planning for family life.